Potential of plant alkaloids as dengue NS3 protease inhibitors: Molecular docking and simulation approach - Muhammad Tahir ul Qamar; Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Muzammal Adeel; Tabeer Fatima (Bangladesh Pharmacological Society, 2014)
Dengue infection has become a worldwide health problem and infection rate is increasing each year. Alkaloids are important phytochemicals of medicinal plant and can be used as vaccine candidates for viruses. Therefore, present study was designed to find potential alkaloids inhibitors against the Dengue virus NS2B/NS3 protease which can inhibit the viral replication inside the host cell. Through molecular docking it was investigated that most of the alkaloids bound deeply in the binding pocket of Dengue virus NS2B/NS3 protease and had potential interactions with catalytic triad. Five alkaloids (6-desmethylthalifaboramin; 3,5-dihydroxythalifaboramine; Betanin; Reserpic acid and  Tubulosine) successfully blocked the catalytic triad of NS2B/NS3 protease and these alkaloids can serve as a potential drug candidate to stop viral replication. It can be concluded from this study that these alkaloids could serve as important inhibitors to inhibit the replication of DENV and need further in-vitro investigations to confirm their efficacy and drug ability.